The effect of listening to Holy Quran recitation on stress among healthy adults: a non-blinded randomized controlled trial - Hanafi, Muchtar; Rahmatillah, Arif; Wiyono, Nanang; Mirawati , Diah Kurnia (Universa Medicina, 2024)
BackgroundStress is the body’s inability to reach a balance between physical or psychological demands and the ability to meet them. Failure to meet these demands has a crucial impact which includes physical, emotional, and behavioral disorders. Recitation of the Quran is believed to cause relaxation by lowering adrenocorticotropic and cortisol hormonal levels. This study aimed to assess the effects of Quran recitation on stress levels using the biofeedback indicators electromyogram, skin conductance, and heart rate among healthy adults. MethodsThis study used a pre- and post-test group design involving 40 males between 19 and 23 years of age, randomized into two groups, i.e. control group (n=20) and Quran recitation listeners (n=20). The subjects were conditioned in a quiet room for 30 minutes before the stress level measurements were taken. The stress level measurements by means of electromyogram, skin conductance, and heart rate were performed with biofeedback before and after giving the stressor tests’ protocol. Statistical analysis using independent t-test was then performed. ResultsThe baseline comparative measurement using biofeedback between control and treatment groups revealed nonsignificant between-group differences in electromyogram, skin conductance, and heart rate (p=0.150; p= 0.389; and p=0.985 respectively). After applying the stress protocol followed by the intervention, the independent t-test revealed significant between-group differences in electromyogram and skin conductance (p= 0.042 and p=0.030), but not in heart rate (p=0.741). ConclusionsOur study demonstrated that Quran recitation has a significant effect in relieving stress levels assessed using biofeedback parameters (electromyogram and skin conductance) among healthy adults.